Deteksi Perubahan Tutupan Lahan Menggunakan Citra Landsat ETM (Enhanced Thematic Mapper) Multi Temporal di Pesisir Utara Pulau Mendanau dan Pulau Batu Dinding, Kabupaten Belitung - Irma Akhrianti; Franto Franto; Eddy Nurtjahya; Indra Ambalika Syari (Akuatik: Jurnal Sumberdaya Perairan, 2018)
Land cover changes is a physical impact which caused by the the existence of human activity that is quite high in parts of the lithosphere of the earth. The change in landscape certainly has a positive correlation with the dynamics of land use in an area, so that regular monitoring needs to be done, because often land use occurs out of control and not even in accordance with its designation. The main problems that occur in Mendanau Isalnd and Batu Dinding Island are the high level of utilization of mangrove ecosystems, the conversion of mangrove land into ecotourism areas, ports area, residental area and mining area (bauxite). This study aims to monitor changes in land cover in the northern coastal areas of Mendanau Island and Batu Dinding Island in Belitung Regency for 6 years (2000, 2002, and 2006) using a remote sensing technology approach, where image data processing refers to a guided classification method combined with check the field. The satellite images used are still classified as low resolution, namely Multitemporal ETM satellite images with ± 10% cloud cover rate. The results showed that, found 6 land cover classes, namely settlement, open land, mangrove vegetation, non-mangrove vegetation, marine waters, and clouds, which can be detected there has been a change in the increase in the area of non-mangrove vegetation by 365.47 ha, while residential areas experienced fluctuating conditions, namely an increase in cover area in 2000-2002 around 111.94 ha, then declined again in 2006 amounting to 61.28 ha. Unlike the case with the area of open land cover and cover of mangrove vegetation which tends to decrease. The area of open land cover in 2000-2002 decreased by 16.96 ha, then declined again in 2006 by 32.32 ha. The cover area of mangrove vegetation in 2000-2002 decreased by 69.5 ha, then decreased again in 2016 amounting to 208.82 ha.